Using Teak Leaves As Natural Dye And An Ecoprinting Material To Imprint Motifs On Silk Fabrics - Baby Ayu; Najmawati Sulaiman; A. Adlin; Nugrah Juniar Umar; Kiranti Maulidya Muntasir; Pahanthihage Dilhari Prasangika (Institut Seni Indonesia Yogyakarta, 2022)
Natural dyes are generally obtained from the extracts of plant parts. Teak leaves produce natural dyes and can be used to create ecoprinted works.This study aimed at utilizing teak leaves as natural dye and as an ecoprinting material imprinted on silk fabrics using alum mordant. The state of the art of this research is the using of teak leaves as natural dye and ecoprint materials on a single piece of silk fabric. The purpose of the study was to get natural colors, to create ecoprinted products, and to add aesthetic and economic value to the fabrics. The research method included the following stages: 1). Dyeing the cloth in TRO solution, 2). Extracting teak leaves, 3). Dyeing the cloth with the teak extract, 4). Ecoprinting with boiling technique, 5). Creating functional product out of the treated fabrics. The resulted extract dye created reddish orange color on the silk fabrics. The ecoprinting using teak leaves on silk fabrics produced the same yet more intense color. After the mordanting process, the shade of the color remained the same. The functional products created were pillow cases.